2019
DOI: 10.1080/15384101.2019.1658477
|View full text |Cite
|
Sign up to set email alerts
|

Mild replication stress causes aneuploidy by deregulating microtubule dynamics in mitosis

Abstract: Chromosomal instability (CIN) causes structural and numerical chromosome aberrations and represents a hallmark of cancer. Replication stress (RS) has emerged as a driver for structural chromosome aberrations while mitotic defects can cause whole chromosome missegregation and aneuploidy. Recently, first evidence indicated that RS can also influence chromosome segregation in cancer cells exhibiting CIN, but the underlying mechanisms remain unknown. Here, we show that chromosomally unstable cancer cells suffer fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 40 publications
5
33
0
1
Order By: Relevance
“…Other studies have reported that mild induced replication stress or intrinsic replication stress in CIN + cells alter microtubule dynamics by increasing microtubule plus-end growth. Merotely and chromosome mis-segregation occurred here in the absence of spindle multipolarity and was entirely due to microtubule alterations [148].…”
Section: Replication Stress and Spindle Microtubulesmentioning
confidence: 67%
See 2 more Smart Citations
“…Other studies have reported that mild induced replication stress or intrinsic replication stress in CIN + cells alter microtubule dynamics by increasing microtubule plus-end growth. Merotely and chromosome mis-segregation occurred here in the absence of spindle multipolarity and was entirely due to microtubule alterations [148].…”
Section: Replication Stress and Spindle Microtubulesmentioning
confidence: 67%
“…In contrast, the Bastian laboratory rescued the increased microtubule polymerization rate in CIN+ cells and in cells treated with APH by using nanomolar doses of Taxol. This treatment rescued the lagging of entire chromosomes, suggesting a synthetic viable constellation in this case [148]. Altogether, these data suggest that chromosomally unstable cells are intrinsically more vulnerable to microtubule-interfering drugs and could benefit from a combination of drugs targeting repair and/or replication in interphase and microtubules in mitosis.…”
Section: Microtubule-targeting Drugsmentioning
confidence: 74%
See 1 more Smart Citation
“…Various abnormalities in chromosomally unstable cancer cells can contribute to the generation of lagging chromosomes including supernumerary centrosomes [6,7] or hyperstable microtubule-kinetochore attachments [8,9]. More recently, we have demonstrated that abnormally increased microtubule plus end assembly rates within mitotic spindles result in the induction of W-CIN in cancer cells [10][11][12][13][14][15][16]. In fact, increased microtubule assembly rates cause merotelic microtubule-kinetochore attachments, lagging chromosomes, and chromosome missegregation [10] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the strong link between increased mitotic microtubule assembly rates and W-CIN, the cancer-associated genetic alterations leading to abnormal microtubule dynamics are not well understood. So far, only a few tumor suppressors and oncogenes including BRCA1, CHK2, AURKA, and CEP72 were shown to be involved in triggering W-CIN by increasing mitotic microtubule assembly rates [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%